Relaksasi Dzikir dalam Menangani Kecemasan bagi Mahasiswa Angkatan 2020 Prodi Tasawuf dan Psikoterapi UIN Sunan Ampel Surabaya - Dzakiyah, Adly Alanda (Proceedings of Student Symposium on Ushuluddin and Islamic Thought, 2024)
This research examines the concept of dhikr relaxation used in dealing with anxiety for students of the 2020 class of the Sufism and Psychotherapy study program at UIN Sunan Ampel Surabaya. Anxiety is a common problem that can be experienced by every individual, one of which is a student. One of the causes of a student experiencing anxiety is because of the final assignment. The study in this research contains the concept of dhikr relaxation which can be used in dealing with anxiety in students of the Class of 2020 Sufism and Psychotherapy study program at UIN Sunan Ampel Surabaya, the application and method of dhikr relaxation in dealing with anxiety in students of the Class of 2020 Sufism and Psychotherapy study program UIN Sunan Ampel Surabaya and the results dhikr relaxation in dealing with anxiety in Class of 2020 students of the Sufism and Psychotherapy study program at UIN Sunan Ampel Surabaya. The research method used is a qualitative method. Data collection was carried out through interviews, questionnaires, observation and documentation studies. This research resulted in the finding that dzikir relaxation can be used as a way to deal with anxiety in students, especially in final semester students who are currently working on their final assignments. By doing dzikir relaxation, you can create a feeling of calm and comfort. So that peace of mind will be felt by those who do dhikr relaxation. Therefore, dhikr relaxation can be used as an option to feel calm and stay away from anxiety disorders.